Use of data mining systems as an enhancement of digital libraries - Miočić, Petra (Array, 2012)
Data mining is one of the fundamental terms in the field of knowledge and information management as well as in knowledge organization. That process is the foundation of many data-bases, and lately, many digital libraries as well . One specific data mining system, Microsoft Pivot, and its application to the digital library is the main interest of this paper. Pivot’s main potentials refer to the visualization and graphical presentation of data, as well as simplifications and enhancements in user’s browsing of large quantities of data and information stored in the library. When using that sort of system, information professional s can choose what types of metadata they will include and make retrievable. One can even go as far to sort items by the colour of their cover. Even though that kind of solution ma y seem unnecessary and maybe even ridiculous to an information specialist, it can be very useful for a student or even to a faculty when they are in search for a specific title. The Pivot system will be implemented at the Library of the Faculty of Humanities and Social Sciences and afterwards tested and compared to the traditional library catalogue by the selected groups of LIS and other departments’ students, librarians and faculty members and a comparative analysis will be made. The goal of the research is to explore the real searching and browsing needs of end-users and to get the users’ viewpoint on the advantages and disadvantages of the traditional library system and the new, applicable, data visualization system.